(untitled) (Research, Society and Development, 2026)
Introduction: In Food and Nutrition Services (FNS), workplace accidents can occur due to inadequate physical layout, deficient machinery and equipment, accelerated work pace, work overload due to understaffing, among other factors. Objectives: To identify the risk of accidents in the Food and Nutrition Service sectors, classify the degree of this risk, and develop a risk map. Methodology: A descriptive study was conducted in a large-scale FNS in a public hospital in the city of Salvador, Bahia, Brazil. Observations in the FNS were recorded in a field diary. The recommendations of Ordinance no25 of the Ministry of Labor and Employment were followed in the development of the risk map. Results: Although the sectors were adequately delimited in the FNS, it was observed that the flows of employees and production were not properly demarcated. In the meal preparation stage for patients and their companions, a high risk of accidents was identified, especially falls and burns. A similar situation was observed during restocking at distribution counters and among workers using equipment shared by different sectors. Final considerations: The Service’s risk map was developed based on a diagnosis of the risks to which workers were exposed. The findings indicated that the factors contributing to accidents were related to insufficient periodic training focused on occupational safety, highlighting the need for structural and organizational improvements, as well as the strengthening of continuous educational initiatives.